Zoonotic Dirofilaria repens (Nematoda: Filarioidea) in Aedes vexans mosquitoes, Czech Republic - Rudolf, Ivo; Šebesta, Oldřich; Mendel, Jan; Betášová, Lenka; Bocková, Eva; Jedličková, Petra; Venclíková, Kristýna; Blažejová, Hana; Šikutová, Silvie; Hubálek, Zdeněk (Parasitology research, 2014)
The surveillance of vectors for arthropod-borne pathogens is nowadays an important tool in surveillance programmes throughout Europe. Whereas many studies have been performed to screen arthropods for viruses or bacterial pathogens, only limited information is available concerning the geographical distribution and vector range of pathogenic filariae in Central Europe. To consider the prevalence of filarial parasites in mosquito vectors, we performed a molecular survey of mosquitoes for filarial DNA. Mosquito collection was conducted at six study sites in the South Moravian region (Czech Republic) close to the borders with Slovakia and Austria from 2009 to 2011. Molecular screening of mosquitoes was conducted using conventional PCR with primers designed to amplify the mitochondrial cytochromoxidase subunit I gene as well as the partial 5.8S ribosomal RNA gene. A total of 13,222 mosquitoes belonging to six species were captured and distributed into 237 pools with different numbers of individuals. Overall, four pools were positive for Dirofilaria repens (a minimum infection rate 0.03%) at two study sites (both natural and urban). Another filarial parasite detected during a study into Aedes vexans mosquitoes revealed the closest homology to Setaria spp. We detected specific D. repens DNA in Ae. vexans mosquitoes for the first time in the Czech Republic and confirmed the circulation of Dirofilaria spp. in a natural focus of infection providing an epidemiological link between autochthonous canine cases and mosquito vectors in the area studied.
Keywords: psi; dirofilarióza; zeměpis; Humans; sekvence nukleotidů; Dogs; Sequence Analysis, DNA; Molecular Sequence Data; Geography; Insect Vectors; molekulární sekvence - údaje; Female; Public Health; veřejné zdravotnictví; lidé; zoonózy; zvířata; Dirofilaria repens; sladká voda; sekvenční analýza DNA; ženské pohlaví; hmyz - vektory; Base Sequence; Fresh Water; nemoci psů; polymerázová řetězová reakce; Czech Republic; Zoonoses; Polymerase Chain Reaction; Aedes; Dog Diseases; Animals; Česká republika; Dirofilariasis